1999
DOI: 10.1002/(sici)1097-0185(19991001)256:2<146::aid-ar5>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Slow tonic muscle fibers in the thyroarytenoid muscles of human vocal folds; a possible specialization for speech

Abstract: Most of the sounds of human speech are produced by vibration of the vocal folds, yet the biomechanics and control of these vibrations are poorly understood. In this study the muscle within the vocal fold, the thyroarytenoid muscle (TA), was examined for the presence and distribution of slow tonic muscle fibers (STF), a rare muscle fiber type with unique contraction properties. Nine human TAs were frozen and serially sectioned in the frontal plane. The presence and distribution pattern of STF in each TA were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 81 publications
(110 reference statements)
1
32
0
7
Order By: Relevance
“…The specificity and characterization of these mAbs against MHC isoforms have been previously established. The mAbs NOQ7-5-4D is specific to type I MHC [7,23], MY-32 to all fasttype MHCs [7,39,40], SC-71 to type IIa MHC [7,25,40,41], ALD-58 to MHC-ton [7,33,42], BA-G5 to MHC-a [7,35], F1.652 to MHCemb [7,35], and N2.261 to MHC-neo [35].…”
Section: Monoclonal Antibodies (Mabs)mentioning
confidence: 99%
See 3 more Smart Citations
“…The specificity and characterization of these mAbs against MHC isoforms have been previously established. The mAbs NOQ7-5-4D is specific to type I MHC [7,23], MY-32 to all fasttype MHCs [7,39,40], SC-71 to type IIa MHC [7,25,40,41], ALD-58 to MHC-ton [7,33,42], BA-G5 to MHC-a [7,35], F1.652 to MHCemb [7,35], and N2.261 to MHC-neo [35].…”
Section: Monoclonal Antibodies (Mabs)mentioning
confidence: 99%
“…The presence of the unusual MHC isoforms in some cranial muscles is most likely associated with their unique functional requirements. For instance, MHC-ton isoform exists only in the muscles that perform fine movements [17,32,33]. The high proportions of the m/u hybrid fibers found in the adult human MH muscle may be suitable for postural and endurance activities of the muscle that are needed to displace and stabilize the mandible and hyoid bones during various upper airway functions.…”
Section: Physiologic Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existence of these fibers was thought to be limited largely to EOM, tensor tympani, and stapedius; however, studies of humans indicate that MIFs are also found in laryngeal muscles and the tongue. 20 In mammalian EOM, two MIFs are present, one in each of the anatomic regions.The global MIF has en-grappe endplates along its length and contracts in a graded or 'tonic' fashion. The en-grappe endplates compose a significantly smaller surface area of the muscle and have very shallow synaptic folds compared to the en-plaque endplates, which are similar in morphology to the endplates of other skeletal muscles.…”
mentioning
confidence: 99%